Trapped In The Digital Rush: The Impact Of Technostress, Digital Work Overload, And Supervisor Support On Employee Wellbeing - Fajar Eryanto Septiawan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
As digital transformation accelerates in the post-pandemic workplace, employees face increasing pressure to remain constantly connected and responsive. While technology enhances flexibility and efficiency, it also introduces new psychological demands that can undermine employee wellbeing. This study investigates the influence of technostress, digital work overload, and supervisor support on employee wellbeing among professionals working in hybrid and digitally integrated organizations in 2025. Grounded in the Job Demands–Resources (JD-R) theory and the Conservation of Resources (COR) model, this research proposes that technostress and digital work overload function as job demands that exhaust personal resources, while supervisor support serves as a critical job resource that can buffer negative effects and promote wellbeing. Data were collected through an online survey involving 210 respondents from various service and technology-based companies operating in Jakarta and Bandung. Results from that technostress and digital work overload have significant negative effects on employee wellbeing, while supervisor support has a significant positive effect. These findings confirm that maintaining digital balance and supportive leadership are essential for sustaining psychological health in the digital work environment. The study contributes to discussions on digital wellbeing in HRM by emphasizing the need for mindful technology use and empathetic leadership in hybrid workplaces.